Leukoplakia in HIV patients and risk of malignancy: A case report - Yuli Fatzia Ossa; Anandina Irmagita Soegyanto; Diah Rini Handjari; Endah Ayu Tri Wulandari (Universitas Airlangga, 2020)
Background: Oral potentially malignant disorder (OPMD) was defined by the World Health Organization (WHO) as an oral lesion which shows abnormalities with potential to become malignant. Leukoplakia is one such OPMD that may present in patients with human immunodeficiency virus (HIV), with the condition of HIV presenting a heightened risk of malignancy. Purpose: This case report aims to describe the initial finding and case management of an oral lesion that was suspected as leukoplakia in an HIV-positive patient on antiretroviral therapy (ART). Case: A 34-year-old male patient was referred to the Oral Medicine Division from an HIV clinic at Dr. Cipto Mangunkusumo General Hospital, Jakarta, with a chief complaint of dental caries. The patient was HIV and hepatitis C positive and already undergoing ART. Case Management: During the intraoral examination, we found multiple caries, poor oral hygiene and a single thin white plaque lesion on the right buccal mucosa around the second and third mandibular molar region. The white plaque was painless, irregular, clearly demarcated, could not be rubbed off and did not disappear when stretched. History of trauma in this area was non-contributory and the lesion had gone unnoticed prior to oral examination. The patient had an existing smoking habit of 25 years. As clinical examination suggested leukoplakia, a biopsy was arranged. Conclusion: Leukoplakia is defined as a potentially malignant lesion. The risk of shifting into malignancy can be higher for patients who are HIV positive. Especially in HIV-positive patients, special measures are needed to prevent shifting into malignancy, such as early detection, elimination of risk factors, performing excisional biopsy and regular intraoral examination.